Предмет: Математика, автор: rusbelyaev95

Преобразуйте в многочлен:
(y+4) ^2
(2x-3y) ^2
(-3a+5)
(-x^2-2x) ^2
(x-6) ^2
(7m+3n) ^2
(-2y+3) ^2
(-x^3-4x) ^2




Ответы

Автор ответа: jangoriunov
1

Ответ:

Пошаговое объяснение:

(y+4) ^2  = y^2+8y+16

(2x-3y) ^2  = 4x^2-12xy+9y^2

(-3a+5) ^2= 9a^2+30a+25

(-x^2-2x) ^2  = x^4+4x^3+4x^2 (?)

(x-6) ^2  = x^2-12x+36

(7m+3n) ^2  = 49m^2+42mn+9n^2

(-2y+3) ^2  = -(2y-3)^2 = -(4y^2+12y+9) = -4^2-12y-9

(-x^3-4x) ^2 = -(x^3+4x)^2 = -x^6-8x^4-16x^2

Похожие вопросы